Pharmacokinetics and Druglikeness of Amoxicillin Drug using SwissADME - Prasetyawan, Fendy; Saristiana, Yuneka; Mildawati, Ratna; Rhomah, Eka Hayati; Fadel, Muhammad Nurul; Besan, Emma Jayanti (Multicore International Journal of Multidisciplinary (MIJM), 2025)
Amoxicillin, a widely utilized semi-synthetic penicillin derivative, remains a cornerstone in treating various bacterial infections. Despite its extensive clinical application, a comprehensive in silico assessment of its pharmacokinetic and "druglikeness" properties using modern computational tools can provide valuable complementary insights. This study employed the SwissADME web platform to meticulously analyze the computed descriptors, physicochemical characteristics, ADME profile, druglikeness, and medicinal chemistry aspects of amoxicillin. The chemical structure of amoxicillin, represented by its SMILES string, was retrieved from the PubChem database and subsequently input into SwissADME for analysis. The results indicate that amoxicillin possesses a molecular weight of 365.40 g/mol and a hydrophilic nature, as evidenced by its consensus LogP value of -0.39 and high water solubility predictions. Its Topological Polar Surface Area (TPSA) is 158.26 Å², and it contains 4 hydrogen bond donors and 6 hydrogen bond acceptors. While the in silico prediction for gastrointestinal (GI) absorption was "Low" (likely due to the high TPSA and hydrophilicity, suggesting reliance on active transport mechanisms in vivo), amoxicillin fully complies with Lipinski's Rule of Five, indicating good oral bioavailability potential. Furthermore, it is predicted not to permeate the Blood-Brain Barrier (BBB) and shows no inhibitory activity against major CYP450 enzymes (CYP1A2, CYP2C19, CYP2C9, CYP2D6, CYP3A4) or P-glycoprotein, minimizing potential drug-drug interactions. The absence of PAINS and Brenk alerts signifies a clean chemical profile regarding assay interference and toxicity flags. Although some stricter druglikeness filters were violated due to its polar nature, amoxicillin's overall in silico profile, combined with its established clinical efficacy, highlights the complex interplay of physicochemical properties and biological transport mechanisms. This study reaffirms amoxicillin's favorable attributes from a computational perspective, serving as a valuable reference for understanding established antibiotics and guiding future antimicrobial design.